OPTIMALISASI PENGADAAN FASILITAS MASJID: PERANAN REMAJA MASJID DALAM MENUNJANG FASILITAS MASJID BABUL JANNAH PANDAN MELALUI TRADISI MA’BORONG BAWANG MERAH DI DESA MUNDAN, KEC. MASALLE, KAB. ENREKANG - Resky Pertiwi Putri; Agung Perdana; Ramlahwati Ramlahwati; Salman Salman (IAI DDI Mangkoso, 2025)
This study aims to analyze the role of mosque youth in supporting the facilities of Masjid Babul Jannah Pandan in Mundan Village, Masalle Subdistrict, Enrekang Regency, through the Ma'borong bawang merah tradition. The research method used a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study show that mosque youth play a significant role in improving the quality of the mosque's facilities through the Ma'borong tradition, which includes: fundraising, maintenance of facilities, and the development of religious activities. This tradition also strengthens solidarity and the community's awareness of the importance of active youth involvement in the development of the mosque. This study contributes to the development of the mosque and the strengthening of the role of youth in the community. The study also found that the Ma'borong tradition has a positive impact on the development of the mosque, such as increasing community awareness of the importance of the youth's role. Additionally, the study revealed that mosque youth have great potential in developing religious activities and preserving local traditions and culture.